Readyness of maintenance organisation in implementing Building Information Modelling (BIM) on maintenance operation / Muhammad Raizzudin Ab Rahsid - Ab Rahsid, Muhammad Raizzudin (Faculty of Architecture, Planning and Surveying, 2013)
Building Information Modeling (BIM) is a new system approach to design, construction and maintenance management in which a digital representation of the building process is being created into facilitating the exchange and interoperability of information in digital format. In Malaysia, this system is still new system especially in maintenance work. In construction it already applies but in maintenance it's still new. Some organization already applied especially private organization, for public organization it's still in phase of trial. The objective of the study includes the level of knowledge of the organization, to identifying the level on BIM tool utilization, identifying the challenges and barriers and strategies for the implementation of Building Information Modeling (BIM) in local maintenance industry. A questionnaire are distributed where responses 30 respondents in the field of Building Facilities management and maintenance. All the questionnaires are answered and duly return the questionnaire. The data collected was analyzed and the conclusion and recommendation are made. In conclusion, the study has identified several strategies for building Information modeling to be implemented and utilized in maintenance services industry.